If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 2(6 + -1x) = 15 + 3(5 + -1x) 7 + (6 * 2 + -1x * 2) = 15 + 3(5 + -1x) 7 + (12 + -2x) = 15 + 3(5 + -1x) Combine like terms: 7 + 12 = 19 19 + -2x = 15 + 3(5 + -1x) 19 + -2x = 15 + (5 * 3 + -1x * 3) 19 + -2x = 15 + (15 + -3x) Combine like terms: 15 + 15 = 30 19 + -2x = 30 + -3x Solving 19 + -2x = 30 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 19 + -2x + 3x = 30 + -3x + 3x Combine like terms: -2x + 3x = 1x 19 + 1x = 30 + -3x + 3x Combine like terms: -3x + 3x = 0 19 + 1x = 30 + 0 19 + 1x = 30 Add '-19' to each side of the equation. 19 + -19 + 1x = 30 + -19 Combine like terms: 19 + -19 = 0 0 + 1x = 30 + -19 1x = 30 + -19 Combine like terms: 30 + -19 = 11 1x = 11 Divide each side by '1'. x = 11 Simplifying x = 11
| 3x-24+30=8x-4+60 | | 80y^3=16y^2 | | 6x+10=2x+34 | | 0.9x=2.52 | | 9(x+2)=5[x-(5-x)] | | 9(6x+2)=288 | | 5+5x=6+4x | | 2(12y-4)=112 | | H=-16t^2+54t+40 | | 6f-3-7f=-8-2f | | 2(3v-8)v= | | 4/x-1=5/x | | 8t^0/2s^-3 | | 2x^2+y^2=2xy+4x | | h-9/j=k | | 6(w-2)+16=4 | | 7x-(5x-15)=36 | | 4y^3+7y^2-20y-35=0 | | 25m+33n-4m-8n+2n+5m= | | X/2*8=6 | | -10b-9=-5b-7b+9 | | x/7-g=a | | x(2x-3)-3x(5-2x)=0 | | 1/6(k)=8 | | 1.6666667x^4-16x^3+36x^2=0 | | y=ax-1 | | R/-4=-15 | | 7m=6m-8 | | 5(a-4)=3(2+a) | | 20x^2+31x=7 | | 1.5x+16.5x+20y=180 | | 2x-2=5(x-3)/11 |